2013
DOI: 10.1007/s11914-012-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate Drug Holiday: Choosing Appropriate Candidates

Abstract: Osteoporosis related fractures contribute to morbidity and mortality in U.S. patients, placing a heavy financial burden on society. Randomized clinical trials involving over 30000 subjects have established bisphosphonates’ efficacy in reducing the incidence of fragility fractures. However, as bisphosphonates are retained for years in the skeleton, reports of adverse events from prolonged use are surfacing in the literature, namely, esophageal cancer, atrial fibrillation, osteonecrosis of the jaw, and atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
0
24
0
4
Order By: Relevance
“…Those who discontinued alendronate experienced a reduction in BMD without an increase in non-vertebral fractures though the risk of clinically recognised vertebral fractures was higher compared with the continuous users. In the continuous user (Alendronate group), the effect of alendronate/ placebo for 10 years was positive with 1-3% increase in BMD, compared to a 5-10% loss in untreated women of similar age [22,95]. In this study markers of bone turnover gradually increased after discontinuation but remained lower than baseline even after 5 years without alendronate [22].…”
Section: Two Important Trials Flex (Fracture Intervention Trial Longmentioning
confidence: 55%
See 1 more Smart Citation
“…Those who discontinued alendronate experienced a reduction in BMD without an increase in non-vertebral fractures though the risk of clinically recognised vertebral fractures was higher compared with the continuous users. In the continuous user (Alendronate group), the effect of alendronate/ placebo for 10 years was positive with 1-3% increase in BMD, compared to a 5-10% loss in untreated women of similar age [22,95]. In this study markers of bone turnover gradually increased after discontinuation but remained lower than baseline even after 5 years without alendronate [22].…”
Section: Two Important Trials Flex (Fracture Intervention Trial Longmentioning
confidence: 55%
“…Existing dental prostheses should be assessed carefully and proposed dental prostheses carefully designed. Mucosal breakdown is the second most common reason for the development of BRONJ lesions [95].…”
Section: Preventionmentioning
confidence: 99%
“…Clinical studies of fracture risk that include a bisphosphonate drug holiday have reported that fracture risk may rise, leading to recommendations that drug holidays be limited to patients with low or moderate fracture risk [29] and then only with intermittent monitoring for bone loss or fracture [30]. Our results show that despite better bone mass and microarchitecture in the drug holiday group than in untreated OVX rats, bone strength is not better.…”
Section: Discussionmentioning
confidence: 68%
“…Figure 8 provides a modified example of such an algorithm that has been proposed by bone health specialists. 41 CONCLUSIONS Treatment of chronic disease states, including osteoporosis, requires careful monitoring. The risk versus benefit of a therapy must be continually evaluated to determine the appropriateness of continued treatment.…”
Section: Discussionmentioning
confidence: 99%